A mediação do SINAES no processo de avaliação das bibliotecas universitárias em Fortaleza - Guerra, Maria Aurea Montenegro Albuquerque (2013)
Thesis submitted for the Mestrado em Avaliação de Políticas Públicas – MAPP/ UFC (Masters in Public Policy Evaluation) with the objective to analyze the process of evaluation of university libraries in Fortaleza carried out by Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira - Inep/MEC (National Institute for Educational Studies and Research Anísio Teixeira) in the context of public policy for higher education. Currently, the evaluation of higher educationinstitutions is carried out by Sinaes. This system was formalized by Law No. 10,861, issued on April 14, 2004. [...]